PENGGUNAAN LAYANAN INFORMASI BERMUATAN PASATOTANG PADA BIMBINGAN KONSELING DALAM MENINGKATKAN MINAT BELAJAR SISWA - Tenri Nyiwi; Suparman Suparman; Junaidi Junaidi (JUPE : Jurnal Pendidikan Mandala, 2022)
This research is inspired and motivated by the lack of innovation in counseling which focuses on motivation and increasing interest in learning for students at SMA Negeri 1 Plampang. Regarding the purpose of carrying out this research is attempted to find out the effect of information services containing pasatotang provided in counseling guidance. This research was conducted using mix-method research, which consisted of analysis of quantitative data and qualitative data which aims to see the effect as well as to describes how information services containing pasatotang have an impact on students at SMA Negeri 1 Plampang. Based on the findings of this study, it was found that information services containing pasatotang had a significant effect on students at SMA Negeri 1 Plampang. this is evident from the results of numerical data processing through statistical analysis, where the average post-test score shows an increase and the significance level on the one t-test is in the amount of 0.000 less than < 0.05 at the 95% significance level, which means that there is an increasing skors compared to the pre-test results before receiving treatment. This means that the alternative hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected.